CRIMINAL LIABILITY OF A WIFE WHO PLANNED THE MURDER OF HER HUSBAND IN THE DECISION OF THE MEDAN DISTRICT COURT NUMBER 284/PID.B/2025/PN MDN - Revalino Perangin-Angin; Halimatul Maryani (Jurnal Ilmu Hukum dan Keadilan, 2026)
Based on the research results, it shows that the process and standard of proof of the element with premeditation in the crime of premeditated murder committed by a wife against her husband begins with collecting various evidence that supports the existence of a prior plan. Then the Judge conducts an objective evaluation of all the evidence and statements submitted. The judge's consideration in assessing the evidence and trial facts related to the motive in the premeditated murder case based on the Medan District Court Decision Number 284 / Pid.B / 2025 / PN Mdn is appropriate. The criminal liability of the wife who planned the murder of her husband based on Decision Number 284 is sentenced to 18 years in prison or 2 years lighter than the maximum prison sentence stipulated by Article 340 of the Criminal Code. The leniency of criminal liability is due to mitigating factors for the defendant, namely the defendant has children, one of whom is still in education.